1999
DOI: 10.1038/sj.bjc.6690439
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutation of PTEN in bladder carcinoma

Abstract: SummaryThe tumour suppressor gene PTEN/MMAC1, which is mutated or homozygously deleted in glioma, breast and prostate cancer, is mapped to a region of 10q which shows loss of heterozygosity (LOH) in bladder cancer. We screened 123 bladder tumours for LOH in the region of PTEN. In 53 informative muscle invasive tumours (≥ pT2), allele loss was detected in 13 (24.5%) and allelic imbalance in four tumours (overall frequency 32%). LOH was found in four of 60 (6.6%) informative, non-invasive tumours (pTa/pT1). We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
105
2
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(116 citation statements)
references
References 24 publications
7
105
2
2
Order By: Relevance
“…In bladder cancer, LOH of chromosome 10q is more frequent in muscle-invasive tumors (Sandberg and Berger, 1994;Cappellen et al, 1997;Cairns et al, 1998;Aveyard et al, 1999). The tumor suppressor gene MMAC1/PTEN has been mapped to 10q23, suggesting that inactivation of this gene may be involved in bladder cancer progression (Sandberg and Berger, 1994;Cappellen et al, 1997;Aveyard et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In bladder cancer, LOH of chromosome 10q is more frequent in muscle-invasive tumors (Sandberg and Berger, 1994;Cappellen et al, 1997;Cairns et al, 1998;Aveyard et al, 1999). The tumor suppressor gene MMAC1/PTEN has been mapped to 10q23, suggesting that inactivation of this gene may be involved in bladder cancer progression (Sandberg and Berger, 1994;Cappellen et al, 1997;Aveyard et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The tumor suppressor gene MMAC1/PTEN has been mapped to 10q23, suggesting that inactivation of this gene may be involved in bladder cancer progression (Sandberg and Berger, 1994;Cappellen et al, 1997;Aveyard et al, 1999). Inactivation of MMAC1/PTEN appears to be an early event in endometrial carcinogenesis (Maxwell et al, 1998;Levine et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46,47 In invasive UCC, PTEN is mutated or shows loss of heterozygosity (LOH) in up to 30% of cases, 9,48,49 whereas this number falls to 6.6% in superficial tumors (pTa/pT1). 42 One group actually reported reduced PTEN protein expression in 94% of advanced stage bladder cancer specimens, whereas only 42% of superficial tumors and 8% of carcinoma in situ (CIS) specimens had reduced PTEN expression. 30 Researchers have also found that PTEN status may be important in influencing response to treatment.…”
Section: Pten As a Tumor Suppressor In Bladder Cancermentioning
confidence: 99%
“…13,17,28,42 PTEN also functions to regulate chemotaxis and cell motility, mechanisms that promote tumor invasion. 9,43-45 As a result, it is not surprising that PTEN loss is associated with aggressive tumor growth, metastases, and worsened patient outcomes.…”
Section: Pten As a Tumor Suppressor In Bladder Cancermentioning
confidence: 99%